Fickle Judgments in Moral Dilemmas: Time Pressure and Utilitarian Judgments in an Interdependent Culture - Hashimoto, Hirofumi; Maeda, Kaede; Matsumura, Kaede (Frontiers in Psychology, 2022)
In the trolley problem, a well-known moral dilemma, the intuitive process is believed to increase deontological judgments, while deliberative reasoning is thought to promote utilitarian decisions. Therefore, based on the dual-process model, there seems to be an attempt to save several lives at the expense of a few others in a deliberative manner. This study examines the validity of this argument. To this end, we manipulate decision-making time in the standard trolley dilemma to compare differences among 119 Japanese female undergraduates under three conditions: intuitive judgment, deliberative judgment, and judgment after a group discussion. The current results demonstrate that utilitarian judgments decreased from 52.9% in the intuition condition to 43.7% in the deliberation condition and 37.0% after the discussion. Additional analysis suggests that the decrease in utilitarian judgments may be related to psychological unwillingness to assume responsibility for the lives of others rather than to an increase in deontological judgments. Finally, these results are discussed from an adaptationist perspective.